Differential assembly diversifies GABA(A) receptor structures and signalling - Sente, Andrija (Nature, 2022)
Type-A γ-aminobutyric acid receptors (GABA(A)Rs) are pentameric ligand-gated chloride channels that mediate fast inhibitory signalling in neural circuits( 1,2 ) and are modulated by essential medicines including general anaesthetics and benzodiazepines( 3 ). Human GABA(A)R subunits are encoded by 19 paralogous genes which can, in theory, give rise to 495,235 receptor types. Yet, the principles governing the formation of pentamers, the permutational landscape of receptors that may emerge from a subunit set and the impact this has on GABA-ergic signalling remain largely unknown. Here, we use cryogenic electron microscopy (cryo-EM) to determine structures of extrasynaptic GABA(A)R assembled from α4, β3 and δ subunits, and their counterparts incorporating γ2 instead of δ subunits. In each case we could identify two receptor subtypes with distinct stoichiometries and arrangements, all four differing from those previously observed for synaptic, α1-containing receptors( 4–7 ). This, in turn, affects receptor responses to physiological and synthetic modulators by creating or eliminating ligand binding sites at subunit interfaces. We provide structural and functional evidence that selected GABA(A)R arrangements can act as coincidence detectors, simultaneously responding to two neurotransmitters, GABA and histamine. Using assembly simulations and single-cell RNA sequencing data( 8,9 ), we calculate upper bounds for receptor diversity in recombinant systems and in vivo. We propose that differential assembly is a pervasive mechanism for regulating the physiology and pharmacology of GABA(A)Rs.